2004
DOI: 10.1002/elan.200403031
|View full text |Cite
|
Sign up to set email alerts
|

Surface Resistance and Potentiometric Response of Polymeric Membranes Doped with Nonionic Surfactants

Abstract: The influence of lipophilic, electrically neutral surfactants added to the membrane on the ion transfer resistance between an aqueous sample and a polymeric ion-selective membrane has been studied by electric impedance spectroscopy and potentiometry. An increase in the surface resistance and a shift of the apparently super-Nernstian response to lower sample ion activities has been observed when using the nonpolar bis(2-ethylhexyl) sebacate as plasticizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…{ The sodium-selective membrane was solvent cast as described 9 and contained 10 mmol kg 21 sodium ionophore tert-butyl calix [4]arene tetraacetic acid tetraethylester, 10 wt% inert lipophilic electrolyte tetradodecylammonium tetrakis(4-chlorophenyl)borate (ETH 500), and the plasticizer o-nitrophenyloctylether and the polymer poly(vinyl chloride) in a 2 : 1 mass ratio. An 8 mm 2 membrane disk was cut from this parent membrane, mounted in a Philips electrode body, backfilled with 0.1 M NaCl and conditioned in 0.1 M NaCl overnight before performing the electrochemical experiments in a described three electrode cell.…”
Section: Notes and Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…{ The sodium-selective membrane was solvent cast as described 9 and contained 10 mmol kg 21 sodium ionophore tert-butyl calix [4]arene tetraacetic acid tetraethylester, 10 wt% inert lipophilic electrolyte tetradodecylammonium tetrakis(4-chlorophenyl)borate (ETH 500), and the plasticizer o-nitrophenyloctylether and the polymer poly(vinyl chloride) in a 2 : 1 mass ratio. An 8 mm 2 membrane disk was cut from this parent membrane, mounted in a Philips electrode body, backfilled with 0.1 M NaCl and conditioned in 0.1 M NaCl overnight before performing the electrochemical experiments in a described three electrode cell.…”
Section: Notes and Referencesmentioning
confidence: 99%
“…Very recently, Muslinkina and Pretsch explored calciumselective membranes doped with the non-ionic surfactants sorbitan monostearate and sorbitan monopalmitate with zero current potentiometry and EIS. 4 The membrane electrodes were formulated to induce a continuous inward flux of calcium ions from the sample to the membrane phase, giving a so-called super-Nernstian potential change at a critical calcium activity. Membranes doped with non-ionic surfactants showed charge transfer resistance changes as observed by EIS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A natural extension of the work by Muslinkina and Pretsch [8,9] was to study the solution adsorption of surfactants onto the polymeric ISE membrane, and this research was undertaken by Xu et al [10]. In this paper [10], EIS showed that solution adsorption of commercially available non-ionic surfactants can be used to reproducibly produce a SAM of the surfactant at the electrode/electrolyte interface and, the electrochemically imposed ion flux at the interface of a chronopotentiometric polymer ISE, is modulated by the SAM, thereby providing a promising experimental tool for the detection of surface confined reactions (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…In two papers by Muslinkina and Pretsch [8,9], these researchers showed that it is possible to dope an ISE polymer membrane cocktail with a prescribed dose of surfactant that yields a self-assembled monolayer (SAM) of surfactant at the membrane surface after casting, and EIS studies showed that the ion transfer resistance, which is a reflection of the kinetics of ion transfer at the membrane/ solution interface, was impeded when the ISE membrane had been blocked by surfactant. A significant outcome of this research was the demonstration that the natural nonionic surfactant, stearyl-b-d-glucopyranoside (S-b-d-GP), is able to form such a SAM, and the SAM of S-b-d-GP undergoes a biorecognition event when contacted with an aqueous solution containing a glucose-specific lectin bound to the protein concanavalin A [8].…”
Section: Introductionmentioning
confidence: 98%